A frustração da expectativa de consumo pela publicidade - Silva, Marcus Vinicius Fernandes Andrade da (2006)
This scientific research deals with some effects of the advertising, as commercial usage, in face of the consumer under the area of the civil liability. The power of the advertising is so great, that revolutionary movements in History justify its practice as a powerful and strategic weapon in search of being able, such as in Nazism. The main focus of interest is the frustration of the expectation of the consumer for the advertising, in the psychological language and of the marketing; there is a dissonance cognitive stimulated for the evolution of the practical one. Some other scientific areas, like psychology, economy, sociology and marketing already have proved of these frustrations. Law system still resists in some aspects to accept such fact as responsible for causing damage. The Legal System does not face such social fact yet, visualizing only the classic molds of the civil liability. The consequence is a paralyze in the Legal System, which would have to take in the new facts and the legal principles are treated indistinctly as the rules of law, depreciating the function of each one in the system. There is a general understanding, with a few exceptions, that the frustration doesn t have enough justification to be a moral damage. The result is an incentive to the suppliers continues with practical abusive. The theory of the games justifies well this fact. This research points out that advertising is not directed indistinctly for the mass, but the specific groups of people